Phytochemical and Metabolomic Profiles of Ethanolic Extract of Curculigo pilosa Rhizomes for Animal Health - Adenike Abosede Adebisi; Adeyinka Oye Akintunde; Grace Oluwatoyin Tayo; Rufus Olusegun Animashaun (ANIMAL PRODUCTION, 2024)
Curculigo pilosa is traditionally used in herbal medicine. This study aims to provide information on the secondary metabolites present in C. pilosa rhizomes powder, considering the growing interest in ethnomedicines in recent times. The rhizomes of C. pilosa were purchased from markets around Ogere, Ogun State, Nigeria. They were authenticated by a botanist, after which the rhizomes were washed and extracted using ethanol. The phytochemical composition and metabolomic profiles of the ethanolic extracts of C. pilosa were determined using gas chromatographic-mass spectrometric (GC-MS) methods. The results showed that the ethanolic extracts of C. pilosa had higher concentrations of phenols (9.27 ± 0.55 mg GAE/g), alkaloids (6.22 ± 1.95 g/100g), flavonoids (0.66 ± 0.05 g/100g), and saponins (0.51 ± 0.02 g/100g), but lower concentrations of glycosides (0.06 ± 0.01 g/100g), steroids (0.20 ± 0.02 g/100g), and tannins (0.09 ± 0.01 g/100g). The twenty-one bioactive compounds found in the extract include tetraethyl silicate (C₈H₂₀O₄Si), benzene, 1,2-dimethoxy- (C₈H₁₀O₂), 5-dodecene, (Z)- (C₁₂H₂₄), 7-tetradecene, (E)- (C₁₄H₂₈), spirohexane-1-carboxylic acid, ethyl ester (C₉H₁₄O₂), 1-dodecanol, 2-octyl- (C₂₀H₄₂O), formaldehyde, methyl (2-propynyl) hydrazone (C₅H₈N₂), D-allose (C₆H₁₂O₆), cyclohexane, 1R-acetamido-2cis,4trans-bis(acetoxy)-3trans-azido- (C₁₂H₂₂N₄O₅), 5-octadecene, (E)- (C₁₈H₃₆), acetamide, 2-(4-hydroxy-3-methoxyphenyl)- (C₁₁H₁₅NO₃), cyclopentanol, 1-(1-methylene-2-propenyl)- (C₉H₁₄O), 1,9-tetradecadiene (C₁₄H₂₆), 9-eicosine, (E) (C₂₀H₄₀), hexadecyl propyl ether (C₁₉H₄₀O), 9-octadecene, (E)- (C₁₈H₃₆), linoleic acid ethyl ester (C₂₀H₃₄O), 2-methyl-Z,Z-3,13-octadecadienol (C₁₉H₃₆O), 3-octadecene, (E)- (C₁₈H₃₆), 3-heptadecenal (C₁₇H₃₂O), tricyclo[5.4.3.0(1,8)] tetradecan-6-one, and 4-ethenyl-3-hydroxy-2,4,7,14-tetramethyl (C₂₀H₃₂O₂). Some of the phytocompounds identified in this study are biologically important and exhibit antimicrobial, antioxidant, and anti-inflammatory properties, which may hold therapeutic potential for both animal and human health.